Metabolome and transcriptome analysis of eleutheroside B biosynthesis pathway in Eleutherococcus senticosus. Issue 6 (June 2022) - Guo, Hong-Yu; Zhang, Jie; Lin, Li-Mei; Song, Xin; Zhang, Duo-Duo; Cui, Ming-Hui; Long, Chang-Wen; Long, Yue-Hong; Xing, Zhao-Bin
Abstract: Eleutheroside B (syringin) is a medicinal active ingredient extracted from Eleutherococcus senticosus (Ruper. et Maxim.) Maxim with high clinical application value. However, its synthesis pathway remains unknown. Here, we analyzed the eleutheroside B biosynthesis pathway in E. senticosus . Consequently, metabolomic and transcriptomic analyses identified 461 differentially expressed genes (DEGs) and 425 metabolites. Further, we identified 7 DEGs and 67 metabolites involved in the eleutheroside B biosynthetic pathway in the eleutheroside B high and low plants. The correlation between the gene and metabolites was explored using the pearson correlation coefficient (PCC) analysis. Caffeoyl-CoA O-methyltransferase, caffeic acid-O-methyltransferase, β-amyrin synthase (β-AS) genes, NAC5, and HB5 transcription factors were identified as candidate genes and transcription factors related to the eleutheroside B synthesis. Eleutheroside B content was the highest at the young stage of the leaves both in the high and low eleutheroside B plants. Quantitative real-time polymerase chain reaction revealed that phenylalanine ammonia-lyase1, cinnamate 4-hydroxylase, β-AS, and leucoanthocyanidin reductase gene had higher expression levels at the young stage of the leaves in the low eleutheroside B plants but lower expression levels in the high eleutheroside B plants. In the present study, we complemented the eleutheroside B biosynthetic pathway by analyzing the expression levels of relevant genes and metabolite accumulation patterns. Abstract : Eleutheroside B; Eleutherococcus senticosus (Ruper. et Maxim.) Maxim; Young stage; Metabolome; Transcriptome.